Psychopathology in Women Incorporating Gender Perspective into Descriptive Psychopathology - Sáenz-Herrero, Margarita (Springer International Publishing : Imprint: Springer, 2015)
Gender has a fundamental influence on the human brain, not only by virtue of biological and hormonal differences between the sexes but also because of the impact of gender-specific cultural, social, anthropological, and environmental factors. Nevertheless, the relation of gender and psychopathology remains a largely neglected field. Gender perspective has been treated as a paradigm in this book on psychopathology because it determines the way in which a psychiatric symptom is defined, perceived, and understood. This conception of gender as being of key importance in the definition of psychiatric symptomatology is exceptional in the literature. The book opens by examining historical and cultural aspects of mental health in women worldwide and the relation of sex, brain, and gender, with coverage of both neurobiological and psychosocial aspects. The significance of gender with regard to specific aspects of psychopathology is then addressed in detail. A wide range of psychological disorders are considered, as well as hormonal influences and issues concerning body image, self identity, sexuality, and life instinct. It is hoped that this book will make a significant contribution in ensuring that gender perspective receives due attention within descriptive psychopathology.